Down payment
160,000×0.20=32,000
128000=X[((1-(1+0.085)^(-25))/0.085]
Solve for x
X=12507.10
Answer:
a) 0.0082
b) 0.9987
c) 0.9192
d) 0.5000
e) 1
Step-by-step explanation:
The question is concerned with the mean of a sample.
From the central limit theorem we have the formula:
![z=\frac{\bar X-\mu}{\frac{\sigma}{\sqrt{n} } }](https://tex.z-dn.net/?f=z%3D%5Cfrac%7B%5Cbar%20X-%5Cmu%7D%7B%5Cfrac%7B%5Csigma%7D%7B%5Csqrt%7Bn%7D%20%7D%20%7D)
a) ![z=\frac{1224-1200}{\frac{60}{\sqrt{36} } }=2.40](https://tex.z-dn.net/?f=z%3D%5Cfrac%7B1224-1200%7D%7B%5Cfrac%7B60%7D%7B%5Csqrt%7B36%7D%20%7D%20%7D%3D2.40)
The area to the left of z=2.40 is 0.9918
The area to the right of z=2.40 is 1-0.9918=0.0082
![\therefore P(\bar X\:>\:1224)=0.0082](https://tex.z-dn.net/?f=%5Ctherefore%20P%28%5Cbar%20X%5C%3A%3E%5C%3A1224%29%3D0.0082)
b) ![z=\frac{1230-1200}{\frac{60}{\sqrt{36} } }=3.00](https://tex.z-dn.net/?f=z%3D%5Cfrac%7B1230-1200%7D%7B%5Cfrac%7B60%7D%7B%5Csqrt%7B36%7D%20%7D%20%7D%3D3.00)
The area to the left of z=3.00 is 0.9987
![\therefore P(\bar X\:](https://tex.z-dn.net/?f=%5Ctherefore%20P%28%5Cbar%20X%5C%3A%3C%5C%3A1230%29%3D0.9987)
c) The z-value of 1200 is 0
The area to the left of 0 is 0.5
![z=\frac{1214-1200}{\frac{60}{\sqrt{36} } }=1.40](https://tex.z-dn.net/?f=z%3D%5Cfrac%7B1214-1200%7D%7B%5Cfrac%7B60%7D%7B%5Csqrt%7B36%7D%20%7D%20%7D%3D1.40)
The area to the left of z=1.40 is 0.9192
The probability that the sample mean is between 1200 and 1214 is
![P(1200\:](https://tex.z-dn.net/?f=P%281200%5C%3A%3C%5C%3A%5Cbar%20X%5C%3A%3C%5C%3A1214%29%3D0.9192-0.5000%3D0.4192)
d) From c) the probability that the sample mean will be greater than 1200 is 1-0.5000=0.5000
e) ![z=\frac{73.46-1200}{\frac{60}{\sqrt{36} } }=-112.65](https://tex.z-dn.net/?f=z%3D%5Cfrac%7B73.46-1200%7D%7B%5Cfrac%7B60%7D%7B%5Csqrt%7B36%7D%20%7D%20%7D%3D-112.65)
The area to the left of z=-112.65 is 0.
The area to the right of z=-112.65 is 1-0=1
Line up the decimal point to each number in order from left to right and subtract to get the difference which should be -0.248
Answer:
13
Step-by-step explanation:
Replace X with 2
Evaluate the function. g(x) = 3x^2 – 2x + 5 Find f(2)
g(x) = 3(2)^2 – 2(2) + 5
Next conduct PEMDAS
Exponents are first so solve 2^2 which is 2 x 2 = 4
g(x) = 3(4) – 2(2) + 5
Next step is multiplication multiply 3 x 4 and 2x2
g(x) = 12 – 4 + 5
conduct adding and subtracting left from right
g(x) = 13
Answer:
175
Step-by-step explanation:
(g*h)(x) is the product of two functions: g(x) = 25 and h(x) = 4 - x.
This product is equal to 100 - 25x.
Substituting -3 for x, we get
(g•h)(-3) = 100 - 25(-3) = 175